(E,E)-1,2-Bis3-(prop-2-yn-1-yloxy)Benzylidenehydrazine - Al-Mehana, W.N.A.; Yahya, Rosiyah; Sonsudin, F.; Lo, K.M. (International Union of Crystallography, 2012)
The molecule of the title compound, C 20H 16N 2O 2, is centrosymmetric, the inversion center being located at the mid-point of the central azine bond. The conformation around the C=N bond is E. The whole molecule (except for the H atoms) is essentially planar, with an r.m.s. deviation of 0.07 Ã. In the crystal, molecules are linked head-to-tail by pairs of C - Hâ¯O hydrogen bonds, forming inversion dimers, and resulting in the formation of chains propagating along 011.